Intellectuals in the Latin Space during the Era of Fascism Crossing Borders (Taylor & Francis, 2020)
This volume investigates a galaxy of diverse networks and intellectual actors who engaged in a broad political environment, from conservatism to the most radical right, between the World Wars. Looking beyond fascism, it considers the less-investigated domain of the 'Latin space', which is both geographical and cultural, encompassing countries of both Southern Europe and Latin America. Focus is given to mid-level civil servants, writers, journalists and artists and important 'transnational agents' as well as the larger intellectual networks to which they belonged. The book poses such questions as: In what way did the intellectuals align national and nationalistic values with the project of creating a 'Republic of Letters' that extended beyond each country's borders, a 'space' in which one could produce and disseminate thought whose objective was to encourage political action? What kinds of networks did they succeed in establishing in the interwar period? Who were these intellectuals-in-action? What role did they play in their institutions' and cultural associations' activities? A wider and intricate analytical framework emerges, exploring right-wing intellectual agents and their networks, their travels and the circulation of ideas, during the interwar period and on a transatlantic scale, offering an original contribution to the debate on interwar authoritarian regimes and opening new possibilities for research.
English
Keywords: Modern History,Latin American History,Military Regimes,Fascism,Far Right Ideology,Corporatism,Ramiro De Maeztu,Pietro Maria Bardi,Universalist Nationalism,Partido Nacional,Centro De Pesquisa,Primo De Rivera Dictatorship,De La Hispanidad,Je Suis Partout,Fustel De Coulanges,Modern Italian Architecture,Radical Conservative Movements,Lucien Rebatet,UNR,Brazilian Integralism,AIB,La Nueva,Piazza Della Vittoria,Catholic Social Teachings,Young Men,Partido Conservador,Le Corbusier,Du Pin,French Fascism,Charles Maurras,Argentinian Institute; thema EDItEUR::N History and Archaeology::NH History; thema EDItEUR::N History and Archaeology::NH History::NHD European history; thema EDItEUR::N History and Archaeology::NH History::NHK History of the Americas